Development and application of an electrochemical sensor modified with multi-walled carbon nanotubes and graphene oxide for the sensitive and selective detection of tetracycline - Wong, Ademar [UNESP]; Scontri, Mateus [UNESP]; Materon, Elsa Maria [UNESP]; Lanza, Marcos R.V.; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2015)
In this work, an electrochemical sensor based on a carbon paste electrode modified with a combination of multi-walled carbon nanotubes functionalized with carboxyl groups (MWCNT-COOH), together with graphene oxide (GO), was developed for the sensitive and selective determination of tetracycline. Electrochemical sensors were constructed using carbon paste modified with 2.6% (w/w) of MWCNT-COOH and 3.1% (w/w) of GO. Under the optimal conditions using adsorptive stripping differential pulse voltammetry (AdSDPV), the sensor showed a linear response for tetracycline concentrations between 2.0 × 10- 5 and 3.1 × 10- 4 mol L- 1, sensitivity of 1.2 × 104 μA L mol- 1, and a detection limit of 3.6 × 10- 7 mol L- 1. The incorporation of GO and MWCNT-COOH in the carbon paste improved the sensitivity, selectivity, and stability of the device. The MWCNT-COOH-GO/CPE sensor was successfully applied for the detection of tetracycline in river water, artificial urine, and pharmaceutical samples, without any need for sample pretreatment. The relative standard deviation (RSD) of the electrochemical measurements was less than 6.0% (n = 3).
Keywords: Adsorptive stripping differential pulse voltammetry; Carbon nanotube; Electrochemical sensor; Graphene oxide; Tetracycline